(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fibriarti BL, Feliatra, Amin B, Darwis. 2021. Biodegradation of LDPE plastic by local strain of Bacillus sp. isolated from Dump Soil Pekanbaru, Indonesia. Biodiversitas 22: 5484-5490. Plastic is a compound resistant to degradation and takes tens to hundreds of years to decompose completely. The diversity of microbial metabolism allows microbes to degrade plastic and utilize it as a source of energy and carbon for growth. One type of plastic widely used in packaging is LDPE (Low-Density Polyethylene). The purpose of this study was to test the ability of local isolates of Bacillus sp. strains BP4 and BP6 isolated from waste soil and to identify them at molecular level. In LDPE plastic degradation test, pieces of LDPE plastic were added as a carbon source to a mineral solution medium and incubated for 30 days on shaker incubator at 150 rpm. The percentage of plastic degradation was calculated by subtracting the percentage of the initial weight of the plastic with the final weight. The test results showed that two isolates i.e. BP4 and BP6 were able to degrade LDPE plastics with degradation percentages of 7.23 ± 0.64% and 8.19 ± 0.12%, respectively. Molecular identification results revealed that Bacillus sp. strain BP4 showed a similarity of 99.72% with Bacillus anthracis strain X11, while Bacillus sp. strain BP6 showed a similarity of 99.93% with Bacillus paramycoides strain 8929.